The Large-Conductance, Calcium-Activated Potassium Channel: A Big Key Regulator of Cell Physiology - Sancho, Maria; Kyle, Barry D. (Frontiers in Physiology, 2021)
Large-conductance Ca2+-activated K+ channels facilitate the efflux of K+ ions from a variety of cells and tissues following channel activation. It is now recognized that BK channels benefit from a particularly impressive range of pre- and post-translational modifications that can dramatically alter its properties and function. This has downstream consequences in affecting cell and tissue excitability, and therefore, function. While finding the “silver bullet” in terms of clinical therapy has remained elusive, ongoing research is providing an impressive range of viable candidate proteins and mechanisms that associate with and modulate BK channel activity respectively. Here, we provide a brief history characterizing BK channel structure and function generally, and discuss important milestones in the efforts to further elucidate the diverse properties ok BK channels in its many forms.